Mineral profile of microbial biomass protein by atomic absorption spectroscopy - Lawas, Phoebe Robles; De Leon, Sonia Y. (1993.)
The mineral profile of microbial biomass protein (MBP) from coconut residue flour (sapal) was evaluated in order to determine the presence and concentration of various essential and toxic trace minerals. In the first phase, precent ash was determined to check the total percent element derived from the atomic absorption (AA) analysis. There is a marked difference in terms of total percent element between the results from the AA analysis and the gravimetric method, for both sapal and MBP. For sapal, the gravimetric value was 1.442% while the AA analysis resulted to 0.9001%. For MBP, gravimetric value was 7.046% whereas AA analysis gave a total of 3.26% element. The second phase, showed no marked difference between the levels of essential trace elements like Fe, Cu and Mn, in sapal and MBP. However, there was a marked enrichment of minerals such as K, Ca, and Mg in MBP. Heavy metals like Hg, Cd and Pb were identified and, except for Hg, were found to have highly increased after fermentation. However, their concentration were way below the tolerable limits set for a 10% substitution of MBP per 100 gram of foodstuffs daily.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour -- Analysis; Single cell proteins